Pemanfaatan Teknologi Mobile Learning dalam Pengembangan Profesionalisme Dosen - Wawan Herry Setyawan (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
Professional lecturers are lecturer professionalism that includes professionalism of teaching, research, and community service. The institution has the responsibility to develop the profession of the lecturer. An important step that can be done by higher education institutions is by developing lecturer profession guidance program covering the field of teaching, research, and community service. The program of developing and fostering the professionalism of the lecturers should be combined with the demands of science, technology, art that develops expansively and qualitatively. The development and professional development of this lecturer can be done through coaching programs based on institutional needs analysis. Programs can be said to succeed if in a lecturer there has been a process of transformation of the program. This transformation process can be seen from two things, namely: (1) improvement of ability in performing a task and (2) behaviour change which is reflected in attitude, discipline and work ethic.